El Sujeto Político como superación del Edipo Occidental a favor de la expresión de los derechos humanos: The Political Subject as Overcoming Western Oedipus in Favor of The Expression of Human Rights - Hernández Montero, Osvaldo Ángel (Universidad del Zulia, 2020)
The following investigation analyzes the Western Oedipus as the psychological substratum of man subsumed into the organization of the contemporary totalitarian state. The counter-ethic that validates the sacrifice of life in favor of the reproduction of merchandise is characterized; justifying the barbarism produced by the sacralization of the globalized market. Consequently, the figure of the Political Subject is insisted on as a disarticulation of the alienating modes of political and economic imposition; in search of the reproduction of life in decent conditions. It is a hermeneutical investigation of a diachronic nature, according to the deductive rationalist approach.